Study on the Effectiveness of Some Multicomponent Material Models with Hyper-viscoelasticity and Stress Softening for SBR/Carbon Black Compounds under two Loading Modes - Mir Hamid Reza Ghoreishy; Foroud Abbassi-Sourki (علوم و تکنولوژی پلیمر, 2023)
Hypothesis: Determination of the parameters of the material models for rubber compounds is usually carried out under simple modes such as uniaxial tension. These models are typically consisted of hyper-viscoelastic and stress-softening equations. However, due to the complicated behaviors of rubbery materials, the effectiveness and accuracy of such models under combined loads of tension, compression, and shear should be verified.Methods: Three rubber compounds were prepared based on SBR reinforced by three different amounts of carbon blacks and underwent uniaxial cyclic under two loading/unloading rates and volumetric tests. The experimental data were used for the determination of parameters of three complex material models using a nonlinear curve fitting method. These models were selected based on the results of our previous findings. We have verified the uniaxial condition of the chosen test method and sample size using finite element method. The computed parameters were employed to simulate cylindrical rubber samples prepared from the same compounds through the finite element method using Abaqus code under compressive-contact loads. The predicted results were next compared with their experimentally measured data.Findings: The results showed that the effectiveness of a material model in the prediction of stress-strain or stress-time behavior of a rubber compound under a simple load case does not necessarily guarantee that the same level of accuracy is obtained for the other loading modes, especially for highly filled compounds.  It is shown here that to obtain accurate results in such cases, in addition to hyper-viscoelastic and stress softening equations, the material model should include proper terms to consider the effect of the filler-filler interactions into account, especially for highly carbon black-loaded compounds. It is found that the best model is the one in which the viscoelastic behavior of the filler-filler structure is independently included.